Travail et émancipation - Lionel Jacquot; Jean-Luc Metzger; Daniel Bachet; Marie-Christine Bureau; Hervé Defalvard; Claude Didry (La Nouvelle Revue du Travail)
Work relationships and human emancipation were both central themes in Karl Marx’s work and key constructs in the sociology of work. Having said that, there has been scant discussion of emancipation in recent years, with most critical work in this field ignoring the topic and getting bogged down in other quarrels. As for research offering a critical perspective of the sociology of work, the main purpose of this corpus has been to highlight new forms of alienation and/or exploitation, neglecting all the while to be as systematic in its look at emancipation thought and practice. The paper, part of the Work and Emancipation strand, seeks to develop a work-related emancipation perspective offering different avenues questioning the capitalist organisation of work.